Modulation Discrimination Interference and Auditory Grouping - Moore, Brian Cecil Joseph; Shailer, Michael J. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 1992)
The detection of a change in the modulation pattern of a (target) carrier frequency, f$_{\text{c}}$ (for example a change in the depth of amplitude or frequency modulation, AM or FM) can be adversely affected by the presence of other modulated sounds (maskers) at frequencies remote from f$_{\text{c}}$, an effect called modulation discrimination interference (MDI). MDI cannot be explained in terms of interaction of the sounds in the peripheral auditory system. It may result partly from a tendency for sounds which are modulated in a similar way to be perceptually `grouped', i.e. heard as a single sound. To test this idea, MDI for the detection of a change in AM depth was measured as a function of stimulus variables known to affect perceptual grouping, namely overall duration and onset and offset asynchrony between the masking and target sounds. In parallel experiments, subjects were presented with a series of pairs of sounds, the target alone and the target with maskers, and were asked to rate how clearly the modulation of the target could be heard in the complex mixture. The results suggest that two factors contribute to MDI. One factor is difficulty in hearing a pitch corresponding to the target frequency. This factor appears to be strongly affected by perceptual grouping. Its effects can be reduced or abolished by asynchronous gating of the target and masker. The second factor is a specific difficulty in hearing the modulation of the target, or in distinguishing that modulation from the modulation of other sounds that are present. This factor has effects even under conditions promoting perceptual segregation of the target and masker.